Knowledge and Attitudes of Maintaining Bone Health among Post-Menopausal Women in Malaysia - Nik Noor Kaussar Nik Mohd Hatta; Mohd Said Nurumal; Muhammad Lokman Muhammad Isa; Azlina Daud; Muhammad Ibrahim; Mohd Ariff Sharifudin; Samsul Deraman (University Library System, University of Pittsburgh, 2019)
Introduction: Public awareness of osteoporosis is low among women in the developing countries. Health education was shown to be effective in improving knowledge and awareness on maintaining bone health. This study aims to identify the level of knowledge and attitudes among post-menopausal women in Malaysia on achieving bone health throughout the menopausal transition period. Methods: A total of 116 post-menopausal female patients of orthopedic menopause clinic were recruited using a purposive sampling approach. Data on osteoporosis awareness and knowledge were collected using validated structured questionnaires Osteoporosis Prevention and Awareness Tool and Osteoporosis Attitude Knowledge Test. The chi-square test was used to determine the association between post-menopausal women's socio-demographic characteristics and their knowledge and attitude towards maintaining bone health. Results: Participants' age ranged between 49 and 82 years (61.84, SD=7.87). The knowledge of osteoporosis varied significantly by age (p=0.014) and education (p=0.001) among the studied population. No significant diffrences were found for participants' attitude towards bone health. Conclusion: This study showed that the age and education levels have significantly different knowledge of bone health.